Characterization of thin-film GaAs diodes grown on germanium-on-insulator on Si substrate - Chia, Ching Kean (2014)
In this study, we report the characterization of thin-film GaAsgrown on germanium-on-insulator (GeOI) on Si substrate. A GaAs/GeOI diode with a 600 nm buffer layer showed a rectification of 1.0 × 107 at ±2 V and had an electrical performance similar to that of the reference sample grown on GaAs substrate. We demonstrate two thin diodes (<350 nm in thickness) that still showed high forward densities and rectification properties. The electrical performances of the diodes degraded as the diode active regions were grown closer to the GaAs/Ge interface due to the increase of defects propagating into the active regions. The experimental results were fitted with the thermionic emission equation and the Frenkel-Poole model.